2015
DOI: 10.1186/2056-5917-1-3
|View full text |Cite
|
Sign up to set email alerts
|

Client, caregiver, and provider perspectives of safety in palliative home care: a mixed method design

Abstract: Background: Palliative care clients with complex needs are increasingly choosing to remain at home for their care. Home represents familiarity, presence of supportive family and friends, potential for normalcy and, a safe haven. The palliative care literature although robust is hardly ever linked with safety and home care. Patient safety has been focused predominantly on institutions without a corresponding level of research or safety initiatives in the home care sector. Although a growing body of research has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 44 publications
0
24
0
5
Order By: Relevance
“…This study provides additional empirical support for the notion that client safety is inextricably linked to the safety of the family/caregiver [ 8 – 11 , 24 , 25 ]. Caregivers, who were predominantly elderly in this study, found themselves taking on increased tasks and responsibilities while trying to balance their own commitments and pre-existing physical and mental health challenges.…”
Section: Discussionmentioning
confidence: 59%
See 4 more Smart Citations
“…This study provides additional empirical support for the notion that client safety is inextricably linked to the safety of the family/caregiver [ 8 – 11 , 24 , 25 ]. Caregivers, who were predominantly elderly in this study, found themselves taking on increased tasks and responsibilities while trying to balance their own commitments and pre-existing physical and mental health challenges.…”
Section: Discussionmentioning
confidence: 59%
“…These findings confirm related work that queries the sustainability of home care delivery systems, which rely on the chronic overloading of numerous caregivers and providers [ 8 – 10 , 41 ]. It follows that initial and ongoing home assessments need to evaluate not only clients’ and caregivers’ health conditions and physical capacities, but also pay close attention to the cognitive, emotional, social, functional, financial, and literacy capacities within the household, as well as their networks of support and willingness to accept responsibilities [ 10 , 11 ]. Home care providers need to be responsive to the capacity, limits, and more importantly, the willingness of clients and their family caregivers to safely manage chronic conditions and medication issues in the home.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations